2021
DOI: 10.1021/acsami.1c22001
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Pressure Sensors Based on MXene/Tissue Papers for Wireless Human Health Monitoring

Abstract: Though the widely available, low-cost, and disposable papers have been explored in flexible paper-based pressure sensors, it is still difficult for them to simultaneously achieve ultrahigh sensitivity, low limit and broad range of detection, and high-pressure resolution. Herein, we demonstrate a novel flexible paper-based pressure sensing platform that features the MXene-coated tissue paper (MTP) sandwiched between a polyimide encapsulation layer and a printing paper with interdigital electrodes. After replaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(122 citation statements)
references
References 57 publications
1
121
0
Order By: Relevance
“…Wearable electronic devices can conform to the skin to capture mechanical 1 , thermal 2 , chemical 3 , electrical 4 , and biological signals 5 , 6 for future health monitoring. The increasing interest in personal air quality monitoring and breath analysis has also spurred the demand for wearable gas sensors to accurately and continuously detect various health-relevant gases 7 – 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Wearable electronic devices can conform to the skin to capture mechanical 1 , thermal 2 , chemical 3 , electrical 4 , and biological signals 5 , 6 for future health monitoring. The increasing interest in personal air quality monitoring and breath analysis has also spurred the demand for wearable gas sensors to accurately and continuously detect various health-relevant gases 7 – 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensor has been successfully used to detect wrist and jugular pulse signals due to its rational structural design and fine material property engineering. Yang et al demonstrated a novel flexible paper-based pressure-sensing platform, which is characterized by Mxene-coated tissue paper (MTP) sandwiched between a polyimide encapsulation layer and printed paper with interdigitated electrodes [ 137 ]. The flexible pressure sensor is integrated with the signal processing and wireless communication module on the mask to be used as a remote breathing monitoring system to wirelessly detect various breathing conditions and breathing abnormalities ( Figure 6 b).…”
Section: Applicationmentioning
confidence: 99%
“…( b ) Breath. Reprinted with permission from reference [ 137 ]. Copyright © 2021, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…For example, in terms of COVID-19 detection, Nguyen et al [ 23 ] integrated a cell-free sensor to detect SARS-CoV-2, and Ye et al [ 24 ] and Fois et al [ 25 ] focused on detecting abnormalities such as coughing behavior. Not specific to COVID-19 but to cope with general respiratory disease, Lazaro et al [ 26 ], Escobedo et al [ 27 ], Zhong et al [ 28 ], Yang et al [ 29 ], Kim et al [ 30 ], and Pan et al [ 31 ] monitored breathing patterns. From a general health monitoring perspective, Gravina et al [ 32 ], Curtiss et al [ 33 ], and Fischer et al [ 34 ] monitored biosignals such as heart rate, respiration rate, and body temperature.…”
Section: Features and Applications Of Current Smart Masks In The Fieldmentioning
confidence: 99%
“…For the facial part of the mask, pressure sensors can be used to obtain the respiration rate and inhalation volume to monitor breathing patterns [ 28 , 29 ]. These are piezoelectric-like sensors that are sensitive enough to respond to exhale volume pressure and flexible, lightweight, and energy-efficient circuits that can fit into the mask.…”
Section: Possible Directions For Feature Extensionmentioning
confidence: 99%